2017
DOI: 10.1152/advan.00034.2017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of a mnemonic-use approach vs. self-study to interpret a lateral chest X-ray

Abstract: The chest X-ray is the most commonly performed medical imaging study; however, the lateral chest film intimidates many physicians and medical students. The lateral view is more difficult to interpret than the frontal view but provides important information that is either not visible or not as evident on frontal view, and inability to read it may lead to missed diagnoses and more expensive imaging. The objective of this study was to assess a novel mnemonic-based approach to teaching medical students to proficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…In this way, it would not be surprising if the students in the intervention group performed significantly better on the posttest assessment exercise than students in the control group, although the students in both groups attended the same courses with the same syllabus and obtained comparable scores during their first academic year. These results reiterate similar findings obtained by a number of other studies that mnemonics help to improve student performance (13,15).…”
Section: Discussionsupporting
confidence: 91%
“…In this way, it would not be surprising if the students in the intervention group performed significantly better on the posttest assessment exercise than students in the control group, although the students in both groups attended the same courses with the same syllabus and obtained comparable scores during their first academic year. These results reiterate similar findings obtained by a number of other studies that mnemonics help to improve student performance (13,15).…”
Section: Discussionsupporting
confidence: 91%
“…There was evidence of considerable heterogeneity in this estimate (I 2 =70%, χ 2 (28)=93.82, p<0.001), although this was not unexpected given the broad inclusion of cognitive reasoning tools. Retrospective exploration of influential studies indicated that Martinez-Franco et al, 49 Talebian et al 50 and Thompson et al 51 seemed to differ from the other studies: their participants had received training with the intervention directly before measuring diagnostic accuracy in the intervention group. Excluding Systematic review these studies reduced heterogeneity (I 2 =38%, χ 2 (25)=40.22, p=0.028) sufficiently to interpret the meta-analysis.…”
Section: Main Analysismentioning
confidence: 97%
“…Mnemonics have proved effective for people in diverse circumstances, such as for children with learning disabilities who are developing reasoning skills (Jangid, Swadia, & Sharma, ), for college students learning vocabulary words (Ocal & Ehri, ), and for people with dementia working to sustain memory (Ford, ). Thompson et al () found that medical students significantly improved their pre‐ and posttest ability to read X‐rays after learning a simple, three‐letter mnemonic.…”
Section: Mnemonic Devicesmentioning
confidence: 99%